1996
DOI: 10.1159/000188802
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Erythropoietin on T-Cell Mitogenic Proliferation in Chronic Renal Failure Patients

Abstract: Uremic patients undergoing hemodialysis (HD) are known to be highly susceptible to infections. Recent data indicate that in addition to its well-known stimulating effects on red cell production, erythropoietin (EPO) may also have immunomodulating properties. The aim of this study was to examine the effect of EPO on lectin-induced T-lymphocyte transformation in uremic patients, as part of its effect on the immune response. Sixteen HD patients and 20 age- and sex-matched healthy controls were compared before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…Previous reports, mostly regarding dialysis patients, have implied that Epo treatment is associated with improved immunological functions [19,20,36,37]. rHuEpo therapy in these patients was associated with repair of T cell functions [36,38], probably via indirect mechanisms [39], as well as normalization of proinflammatory and anti-inflammatory cytokine levels [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports, mostly regarding dialysis patients, have implied that Epo treatment is associated with improved immunological functions [19,20,36,37]. rHuEpo therapy in these patients was associated with repair of T cell functions [36,38], probably via indirect mechanisms [39], as well as normalization of proinflammatory and anti-inflammatory cytokine levels [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…rHuEpo therapy in these patients was associated with repair of T cell functions [36,38], probably via indirect mechanisms [39], as well as normalization of proinflammatory and anti-inflammatory cytokine levels [40,41]. The discrepancies in data on dialysis patients, showing in some cases increased antibody response to an administered antigen [19,24], and in others no statistically significant difference in the level of antibodies detected [25] deserve proper attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several investigators demonstrated that EPO treatment causes an increase in the peripheral thrombocyte count and an improvement in the hemostatic defect of uremia in HD patients [3, 4]. We have previously shown that EPO improves T cell mitogenic proliferation [5]. EPO can influence granulocytic-monocytic progenitor growth and numbers, but the data are conflicting, as some investigators have reported an increase in numbers [6], whereas others reported no change or a decrease [7, 8, 9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that better cutaneous reactivity is not related to the upregulation of IL-2 or OKT3 receptors or increase in cytokine levels. A previous study (12) showed better lymphocyte mitogenic response to OKT3 in dialysis patients with partially corrected anemia using rHuEPO. In our study, CD8 counts were significantly higher in the anemic group over time.…”
Section: Discussionmentioning
confidence: 85%